Embarrassment : poise and peril in everyday life - Miller, Rowland S. (Emotions and social behavior, 1996)
Embarrassment as a basic emotion Embarrassing circumstances A catalogue of embarrassments The development of embarrassment Personality and culture The causes of embarrassment Signs of embarrassment Responses to embarrassment Overcoming embarrassment